The pregnancy factor: the prevalence of depression among women living with HIV enrolled in the African Cohort Study (AFRICOS) by pregnancy status - Jones, Milissa U.; Esber, Allahna L.; Dear, Nicole; Bahemana, Emmanuel; Kibuuka, Hannah; Iroezindu, Michael; Maswai, Jonah; Owuoth, John; Polyak, Christina S.; Ake, Julie A.; Crowell, Trevor A.; Hickey, Patrick W. (Archives of Women's Mental Health, 2021)
Among Sub-Saharan African women living with HIV (WLWH), pregnancy creates unique stressors that may cause depression. We describe the prevalence of depression among WLWHenrolled in the African Cohort Study (AFRICOS) by pregnancy status and describe factors associated with depression. WLWH < 45 years of age underwent six-monthly visits with depression diagnosed using the Center for Epidemiological Studies-Depression scale. Visits were categorized as “pregnant;” “postpartum” (the first visit made after the last pregnancy visit), and “non-pregnant.” The prevalence of depression was calculated for each visit type and compared using prevalence odds ratios (POR) with 95% confidence intervals (CI). Logistic regression with generalized estimating equations was used to evaluate sociodemographic factors associated with depression. From January 2013 toMarch 1, 2020, 1333 WLWH were enrolled, and 214 had pregnancies during follow-up. As compared to the prevalence of depression during “non-pregnant” visits (9.1%), depression was less common at “pregnant” (6.3%; POR = 0.68 [CI: 0.42, 1.09]) and “postpartum” (3.4%; POR = 0.36 [CI: 0.17, 0.76]) visits. When controlling for other factors, the visit category was not independently associated with depression. Visit number, study site, employment status, and food security were independently associated with decreased odds of depression. We observed a lower prevalence of depression during pregnancy and the postpartum period than has been previously described amongWLWH during similar time points.We observed protective factors against depression which highlight the impact that holistic and consistent health care at HIV-centered clinics may have on the well-being ofWLWH in AFRICOS.
Keywords: HIV; Pregnancy; Depression; Women living with HIV (WLWH); Africa; AFRICOS